PENGARUH LEVERAGE, PROFITABILITAS, SIZE, UMUR PERUSAHAAN DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi pada Perusahaan Pertambangan yang Listing di BEI tahun 2004-2008) - Susilatri '; Restu Agusti; Deri Indriani (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
The purpose of this research is to exam the Effect of Leverage, Profitability, Size,Age and Size of Board of Director to Corporate Social Responsibility. The populationof this research is firms listed in Indonesia Stock Exchange during periods 2004 to2008. The sample of this research is mining firms. The samples choice usingpurposive sampling method and resulting 10 firms. Statistic methods using multipleregression analysis. The result indicates that Leverage, Profitability, Size, Firm Ageand Size of Board of Director variables respectively has significantly influence toCorporate Social Responsibility.